Low-dose corticosteroid therapy for cardiogenic shock in adults (COCCA): study protocol for a randomized controlled trial - Mekontso Dessap, Armand; Bagate, François; Delmas, Clément; Morichau-Beauchant, Tristan; Cholley, Bernard; Cariou, Alain; Lattuca, Benoit; Moussa, Mouhamed; Mongardon, Nicolas; Fard, Damien; Schmidt, Matthieu; Bouglé, Adrien; et al. (Current controlled trials in cardiovascular medicine, 2022)
Background Cardiogenic shock (CS) is a life-threatening condition characterized by circulatory insufficiency caused by an acute dysfunction of the heart pump. The pathophysiological approach to CS has recently been enriched by the tissue consequences of low flow, including inflammation, endothelial dysfunction, and alteration of the hypothalamic-pituitary-adrenal axis. The aim of the present trial is to evaluate the impact of early low-dose corticosteroid therapy on shock reversal in adults with CS. Method/design This is a multicentered randomized, double-blind, placebo-controlled trial with two parallel arms in adult patients with CS recruited from medical, cardiac, and polyvalent intensive care units (ICU) in France. Patients will be randomly allocated into the treatment or control group (1:1 ratio), and we will recruit 380 patients (190 per group). For the treatment group, hydrocortisone (50 mg intravenous bolus every 6 h) and fludrocortisone (50 μg once a day enterally) will be administered for 7 days or until discharge from the ICU. The primary endpoint is catecholamine-free days at day 7. Secondary endpoints include morbidity and all-cause mortality at 28 and 90 days post-randomization. Pre-defined subgroups analyses are planned, including: postcardiotomy, myocardial infarction, etomidate use, vasopressor use, and adrenal profiles according the short corticotropin stimulation test. Each patient will be followed for 90 days. All analyses will be conducted on an intention-to-treat basis. Discussion This trial will provide valuable evidence about the effectiveness of low dose of corticosteroid therapy for CS. If effective, this therapy might improve outcome and become a therapeutic adjunct for patients with CS. Trial registration ClinicalTrials.gov , NCT03773822 . Registered on 12 December 2018